Hikmah Kesehatan dalam Ibadah: Perspektif Kitab I'jāz Ṭibbī fī al-Qur’ān Karya Dr. Sayyid al-Jumaili - Mohammad Faza Hidayat (AL-BAYAN INSTITUTE, 2025)
This article discusses the medical and psychosocial aspects of three major Islamic rituals; ablution (wudu), prayer (shalat), and fasting (sawm) based on the analysis of Dr. Sayyid al-Jumaili in I'jāz Ṭibbī fī al-Qur’ān. Through a literature review, it is evident that these religious practices not only hold spiritual significance but also have positive effects on the physical and psychological health of Muslims, emphasizing principles of cleanliness, discipline, and balanced living. The integration of medical and religious perspectives demonstrates how Islamic law remains relevant in the context of modern health